Pengaruh Religiusitas dan Kesadaran Halal (Halal Awareness) terhadap Keputusan Pembelian Produk Halal : Studi Kasus pada Mahasiswa FAI UMSU - Revita Sari; Muhsin Lambok Ilvira (Jurnal Multidisiplin Indonesia, 2026)
Religiosity also plays an important role in influencing consumers' purchasing decisions. This includes the influence of spiritual values, adherence to religious teachings, and worship practices on consumer purchasing preferences, particularly regarding products or services that align with the principles of their religion. Therefore, it is important to understand how religiosity is measured and applied within the context of Indonesian society today. In addition to religiosity, halal awareness regarding halal products is an important aspect of purchasing decisions. Religiosity and awareness of halal products are two key factors that influence the purchasing decisions of Muslim consumers. This study is a quantitative study aimed at identifying and analyzing the influence of religiosity and halal awareness on purchasing decisions, using a case study of students at the Faculty of Islamic Studies (FAI) of UMSU. The analysis was conducted through research instrument testing, classical assumption testing, followed by multiple linear regression analysis. The results of the analysis indicate that, both partially and simultaneously, the variables of religiosity and halal awareness have a significant effect on the purchasing decision variable.